2019
DOI: 10.1038/s41598-019-46858-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Analysis of Annealing Temperature of High-Molecular Weight Hole Transport Layer for Quantum-dot Light-emitting Diodes

Abstract: In this study, we introduce optimization of the annealing conditions for improvement of hardness and hole transporting properties of high-molecular weight poly [9, 9-dioctylfluorene-co-N-(4-(3-methylpropyl)) diphenylamine] (TFB) film used as a Hole Transport Layer (HTL) of Quantum-dot Light-emitting Diodes (QLEDs). As annealing temperatures were increased from 120 °C to 150 °C or more, no dissolving or intermixing phenomena at the interface between HTL and Quantum-Dot Emission Layer (QDs EML) was observed. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…TSP was successfully demonstrated by using the fabricated transparent electrode with patterned aluminum thin film despite of the roughness of the electrode. The gap between the upper and lower electrode was far from the On the other hand, the non-uniform thin film might be disadvantages to the devices with the structure of stacked thin film such as thin film solar cells 38 , 39 and light emitting diodes 40 , 41 . The roughness of the electrodes might result in electrical nonuniformity and leakage current sometimes in severe cases.…”
Section: Resultsmentioning
confidence: 99%
“…TSP was successfully demonstrated by using the fabricated transparent electrode with patterned aluminum thin film despite of the roughness of the electrode. The gap between the upper and lower electrode was far from the On the other hand, the non-uniform thin film might be disadvantages to the devices with the structure of stacked thin film such as thin film solar cells 38 , 39 and light emitting diodes 40 , 41 . The roughness of the electrodes might result in electrical nonuniformity and leakage current sometimes in severe cases.…”
Section: Resultsmentioning
confidence: 99%
“…CHB and ClNaph have high boiling points and were not considered in this experiment. Hexane, used in our previous studies [ 24 ], has a low boiling point, which is advantageous for achieving effective solvent evaporation with annealing of QD EML. However, the low viscosity of hexane makes it unsuitable for use as a single solvent in ink-jet printing, and so the cosolvent process with oDCB was used to control the ink solution properties.…”
Section: Resultsmentioning
confidence: 99%
“…Toluene, used to disperse the TFB film used as HTL, is not an orthogonal solvent with hexane and oDCB in QD EML. The organic solvents used in the formation of the two layers (HTL and QD EML) may interact with each other and adversely affect QLEDs, by such processes as dissolving, intermixing, pinhole formation, and dewetting; however, in our previous research, such processes were not found in TFB under 150 °C annealing conditions [ 24 ]. In this experiment, the annealing temperature of TFB was fixed at 150 °C.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the mobility of TFB and the CBP-doped TFB HTL, devices with an ITO/PEDOT:PSS/HTL/MoO 3 /Ag structure were fabricated. , Figure S7 gives the J – V features of TFB as well as CBP-doped TFB devices, from which the hole mobility can be calculated according to space-charge-limited-current region (SCLC) with Child’s law where L is the thickness of the HTL films and V , μ, ε, ε 0 , and J are the applied voltage, carrier mobility, relative dielectric constant, vacuum permittivity, and current density, respectively. By assuming that ε = 3.5, the calculated hole mobilities of CBP-doped TFB and TFB are ∼7.8 × 10 –3 and 1.0 × 10 –2 cm 2 v –1 s –1 , respectively. , Therefore, we can conclude that the introduction of CBP adjusts both the energy level and the hole mobility, which leads to the barrier-free and balanced combination of holes and electrons in the PNC EML and ultimately enhances the luminance and efficiency of the CPZI PNC LEDs. Additionally, the time-resolved PL decay of the CPZI PNC film (Figure d) shows that the average lifetime (τ avg ) of the CPZI PNC film is 22 and 32 ns for the TFB-only sample and the CBP-doped TFB sample.…”
mentioning
confidence: 81%
“…By assuming that ε = 3.5, the calculated hole mobilities of CBP-doped TFB and TFB are ∼7.8 × 10 −3 and 1.0 × 10 −2 cm 2 v −1 s −1 , respectively. 34,35 Therefore, we can conclude that the introduction of CBP adjusts both the energy level and the hole mobility, which leads to the barrier-free and balanced combination of holes and electrons in the PNC EML and ultimately enhances the luminance and efficiency of the CPZI PNC LEDs. Additionally, the time-resolved PL decay of the CPZI PNC film (Figure 4d) shows that the average lifetime (τ avg ) of the CPZI PNC film is 22 and 32 ns for the TFB-only sample and the CBP-doped TFB sample.…”
mentioning
confidence: 94%